Effectiveness of artificial diet enriched by spinach extract on molting stimulation to produce soft shell crab - Siti Aslamyah; Yushinta Fujaya (Jurnal Akuakultur Indonesia)
Artificial feed is an alternative media applications spinach extract (EB) that is known to contain molting stimulant. However, utilization of the artificial feed is related to its expensive cost, with a very high protein concentration since it's mainly produced from fish based materials, so need to be studied artificial feed formulation with substitution of vegetable material in stimulating molting and growth of mud crabs. Four formula artificial feed enriched EB (700 ng/g crab) used in this study were feed A (fish, crab shells, and cassava), feed B (fish, silage, shell crab, and cassava), feed C (fish, silage, shell crab, soy flour, and cassava), and feed D (fish, silage, shell crab, soy flour, corn starch, and pollard), trash fish and feed A without EB as control. During the test, mud crab intermolt phase was culture individually in crab box placed in pond. The results showed that the percentage of molting and weight growth in their respective in the feed A (44% and 41.96%); feed B (56% and 31.57%); feed C (74% and 23.20%); feed D (50% and 39.15%); trash feed control (24% and 50.66%); and feed A without EB (28% and 35.11%). An opposite phenomenon, where the feed C with the highest percentage of molting but with the lowest growth rate, the opposite occurs in the control of trash feed. This is apparently the effect of spinach extract as a stimulant molting, where performance can be optimized with a complete and balance nutrient composition. This prediction is supported by the analysis of protein content of crabs tested at the highest feed C treatment compared with the control feed.